2023
DOI: 10.1177/21501351231157572
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Mitral Regurgitation Repair Based on Carpentier's Classification: Long-Term Outcomes

Abstract: Background There are few reports of the outcomes of standardized surgical management addressing the etiologic and morphologic aspects of mitral valve malformation according to Carpentier's classification. This study aimed to evaluate the long-term outcomes of mitral valve repair in children according to Carpentier's classification. Methods Patients who underwent mitral valve repair at our institution between 2000 and 2021 were retrospectively reviewed. Preoperative data, surgical techniques, and outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…On the other hand, in a subgroup analysis of patients with two-ventricle Fontan, they found that the larger rudimentary ventricular end-diastolic volume/dominant ventricular enddiastolic volume ratio was associated with significantly higher dominant ventricular end-diastolic pressure and a significant decrease of maximum oxygen consumption (VO 2 max). 1 The findings of the study by Miwa and colleagues are in line with a number of recent studies that demonstrated again no advantage of having a larger rudimentary ventricle on Fontan outcomes. 2,3 These findings challenge the intuitive notion that having a larger rudimentary ventricle might be advantageous for adding additional squeezing power to the dominant ventricle; thus, a greater contribution to stroke volume.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, in a subgroup analysis of patients with two-ventricle Fontan, they found that the larger rudimentary ventricular end-diastolic volume/dominant ventricular enddiastolic volume ratio was associated with significantly higher dominant ventricular end-diastolic pressure and a significant decrease of maximum oxygen consumption (VO 2 max). 1 The findings of the study by Miwa and colleagues are in line with a number of recent studies that demonstrated again no advantage of having a larger rudimentary ventricle on Fontan outcomes. 2,3 These findings challenge the intuitive notion that having a larger rudimentary ventricle might be advantageous for adding additional squeezing power to the dominant ventricle; thus, a greater contribution to stroke volume.…”
supporting
confidence: 82%
“…On the other hand, in a subgroup analysis of patients with two-ventricle Fontan, they found that the larger rudimentary ventricular end-diastolic volume/dominant ventricular end-diastolic volume ratio was associated with significantly higher dominant ventricular end-diastolic pressure and a significant decrease of maximum oxygen consumption (VO 2 max). 1…”
mentioning
confidence: 99%